A note on reactive transitions and Reo connectors - Figueiredo, Daniel (2019)
The structure of a reactive transition system can to be modified on the fly by e.g. removing, reversing or adding new transitions. The topic has been studied by D. Gabbay and his collaborators in different contexts. In this paper we take their work a step further, introducing a suitable notion of bisimulation and obtaining a Hennessy-Milner theorem with respect to a hybrid logic in which transition properties can be expressed. Our motivation is to provide a characterisation of equivalence for such systems in order to exploit their possible roles in the formal description of software connectors in \reo, either from a behavioural (semantic) or spatial (syntactic) point of view.